Analisis Aliran Daya 9 Bus Pada Saluran Transmisi 150 Kv Sub Sistem Riau Menggunakan Metode Gauss Seidel - Sandi, Rio Aditya Febri; Suwitno, Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Transmission lines are tools used to channel electricity from power plants to distributor stations to electricity users. Electricity systems continue to develop, ranging from using one machine to many machines (multi-machines). One analysis that can be done on interconnection systems when the state is steady (tunak or steady state) is the study of power flow. The study of power flow will ensure that the new power system can meet electricity needs economically, efficiently and safely. In this study the method used is gauss seidel method with the help of MATLAB software. From the research conducted, the plant data obtained power of 328.5 MW. While the power that arises between the channels between Koto Panjang to Kota Pinang the active power is 4977,388 KW and the reactive power is J7685,092 KW. So the total power lost from the Koto Panjang transmission line to Kota Pinang amounted to 9156,147 KW or equal to 9.1 MW. So the percentage of lost power that occurs in the channel is 2.78%. Keyword : transmission line, power flow, gauss seidel